Ziemianie w przemyśle drzewnym Królestwa Polskiego (1870–1914) - Ziomek, Wojciech (Studia z Historii Społeczno-Gospodarczej XIX i XX Wieku, 2010)
Participation of landowners in the wood industry od the Polish Kingdom in the years 1870–1914 was limited mainly to the sawmilling industry. Landowners’ companies were 80% of establishments and over 60% of production’s value. The reason for such a large share was possession by the landowners, resource base, which accounted for forests. Another important reason was the spatial decentralizing of the industry. Landowners played a huge role in the production of furniture, creating in 1872 large bent furniture factory in Wojciechów, which, after 1904, employed a total of more than 1,500 people. In other sectors of the Polish Kingdom’s timber industry, gentry did not play a greater role.